Vascular medicine a companion to Braunwald's heart desease - Creager, Mark A.; Beckman, Joshua A.; Loscalzo, Joseph (Elsevier/Saunders, 2013)
Focuses on vascular diseases. This title offers an understanding of vascular biology with reviews of pathophysiology, diagnosis, and management. It equips you to effectively evaluate patients with a range of vascular diseases, and to implement the most appropriate diagnostic and therapeutic strategies available.